Integrated Product Development in Rhinoplasty:A Case Study - YANG Xiaoli; LIU Kai; WU Chunmao (东华大学学报（英文版）, 2023)
R608; The 3D simulation in preoperative design for nasal plastic surgery was studied to help patients see the postoperative effects and reduce medical disputes.The study developed and clinically tested an innovative design for surgical guides for nasal plastic surgery,which showed positive results in patient satisfaction and accuracy in achieving the preoperative simulated effect.The study also investigated the process of designing and producing nasal prostheses and how patient feedback could be obtained using third-party social media voting.Patient satisfaction information was collected and evaluated using the Likert scale,and the data statistical analysis was carried out with the SPSS19.0 software.More than 94.1％of the patients were satisfied with the postoperative results.The study provides a good reference case for the integration of knowledge and skills from the medicine,design,and engineering fields in the development of medical devices.